Capital fictício e financeirização: um balanço crítico - Santos, Thiago José Nogueira Rodrigues dos (2020)
This research establishes a critical balance about fictitious capital and financialization. Specifically, one of the purposes is to apprehend the own movement of fictitious capital in the capitalist mode of production, while the other objective is to conceive the financialization as a historical and central phenomenon in contemporary capitalism. Since the 1970s / 80s, and with the greatest acceleration in the 2000s, the financial dimension keeps exacerbate the volume of financial securities and innovations of complex financial instruments. These provide the right to periodic income and can be traded in various markets. However, these securities do not act in the valorization process of capital, but their remuneration comes from the appropriation of surplus value, denominating fictitious capital. The hypothetical core is that in fictitious capital, the price and interest categories have singularities when compared to the interest bearing capital. The development of theoretical analysis follows three central procedures. The first chapter refers to Karl Marx's contributions to O Capital. In this sense, the categories of interest-bearing capital, fictitious capital and monetary capital are compared, while the second chapter is concerned with the bibliographical revision about financialization from interpreters of the critique of political economy until uncover the magnitude of financialization through descriptive statistics. In the laste chapter, it is established, conclusively, the relationship between fictitious capital and financialization. It is understood that the evolution of financialization unfolds as a result of the process of production of capital, however, will take place mainly through fictitious capital